Indonesian Defense Management Models Are Adaptive And Competitive (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2020)
This research aims to study and describe the existing conditions of Indonesia's current defense management and analyze and develop an adaptive and competitive Indonesian defense management model. This research is a descriptive type with a qualitative approach. The nature of this research is exploratory and qualitative analysis techniques which consist of five stages, namely data collection and assessment, data reduction, data presentation, data validity checking, and drawing conclusions. The results of this study are that currently the defense management carried out by Indonesia still has some gaps and weaknesses where the defense management model has not been developed holistically, where the management of national defense and security has not been interpreted as a whole system. Considering that the implementation of security and defense must be comprehensively carried out as an integrated security and defense system, whose output is of course in addition to the realization of a component of the national defense and security force, including citizens who have strong national resilience. Then, the national defense management model that is found can improve coordination and cooperation between the Ministry of Defense and related institutions in strengthening defense and improving national security as a whole.